Modifications Of Nk-92mi Cell Line Through Third Generation Lentiviral Vector - Chin, Ding Sheng (2023)
In this study, NK-92MI cell line was transduced with RRL lentivirus carrying the genes for either intracellular GFP or surface CD16 receptor, with the addition of polybrene polycation. Results showed that GFP expression averaged at 3.49 % without polybrene and averaged at 7.18 % when polybrene was added. Extracellular CD16 expression averaged at 1.03 % without polybrene and increased to an average of 3.12 % with polybrene. This study demonstrated the feasibility of using the third generation RRL lentiviral vector for NK cell transduction.